Political consequences of complexity Carlos (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
Studies and work on complexity are increasing all over the world. However, there is not one study that explicitly considers the political implications of understanding and explanations of non-linear complex phenomena. This paper explores the most important political consequences of the sciences of complexity and intends to fill a gap in the literature. I shall claim that the political implications of complexity do include policies but they encompass mainly politics in the largest and strongest sense of the word. This argument is supported by three main ideas: firstly, the sciences of complexity are introduced and several derivations are sketched out; secondly, the political implications are considered and; thirdly, the inner relationships between scientific and political revolutions are highlighted. Finally, several conclusions are drawn.
Keywords: The complexity science; Epistemology; Philosophy of Social Sciences; Sivil society; The State